Correlation between association of hypothyroidism and cardiovascular risk indices - Mathur, Rajendra Datt; Gupta, Rameshwar Prasad; Gupta, Deepak; Mathur, Reenika; Bhargav, Ajay Kumar (International Journal of Advances in Medicine, 2018)
Background: Association of hypothyroidism and cardiovascular diseases are important in development of Atherosclerosis. Hypothyroidism and sub clinical hypothyroidism reported highly risk factors due to lipid levels dearranged. Present study to demonstre of correlation of hypothyroidism and cardiovascular disease. Methods: The present study has carried out in the department of medicine and Biochemistry SRG Hospital and associated hospital, Jhalawar Medical College Jhalawar (Raj.) Total 100 Hypothyroidism cases and 100 euthyroidism subject were included in the study Information regarding clinical history were recorded in self Constructed present questionnaires Patients were examined and estimated TSH, T3, T4 total Cholesterol, LDLc, HDCc, TG data were analyzed by SPPS version 20.0. Results: Present study demonstrated increased levels of total cholesterol, LDH, VLDLC and TG and decreased level of HDLC and increased TSH level and decreased T3 and T4 Level in hypothyroidism cases when compared with euthyroid cases It was found significant. Conclusions: In present study hypothyroidism and hormone Level (TSH, T3, T4) and lipid level dearranged values are associated with development cardiovascular disease atherosclerosis.